The role of peripheral β-amyloid in insulin resistance, insulin secretion, and prediabetes: in vitro and population-based studies - Xu, Zihui; Chen, Juan; Wang, Pei; Li, Linyan; Hu, Shan; Liu, Hongjie; Huang, Yue; Mo, Xiaoxing; Yan, Hong; Shan, Zhilei; Wang, Di; Xu, Jian; et al. (Frontiers in Endocrinology, 2023)
Background: Previous experimental studies have shown that mice overexpressing amyloid precursor protein, in which β-amyloid (Aβ) is overproduced, exhibit peripheral insulin resistance, pancreatic impairment, and hyperglycemia. We aimed to explore the effects of Aβ on insulin action and insulin secretion in vitro and the association of plasma Aβ with prediabetes in human.We examined the effects of Aβ40 and Aβ42 on insulin-inhibited glucose production in HepG2 cells, insulin-promoted glucose uptake in C2C12 myotubes, and insulin secretion in INS-1 cells. Furthermore, we conducted a case-control study (N = 1142) and a nested case-control study (N = 300) within the prospective Tongji-Ezhou cohort. Odds ratios (ORs) and 95% confidence intervals (CIs) for prediabetes were estimated by using conditional logistic regression analyses.In the in vitro studies, Aβ40 and Aβ42 dose-dependently attenuated insulin-inhibited glucose production in HepG2 cells, insulin-promoted glucose uptake in C2C12 myotubes, and basal and glucose-stimulated insulin secretion in INS-1 cells. In the case-control study, plasma Aβ40 (adjusted OR: 2.00; 95% CI: 1.34, 3.01) and Aβ42 (adjusted OR: 1.94; 95% CI: 1.33, 2.83) were positively associated with prediabetes risk when comparing the extreme quartiles. In the nested casecontrol study, compared to the lowest quartile, the highest quartile of plasma Aβ40 and Aβ42 were associated with 3.51-fold (95% CI: 1.61, 7.62) and 2.75-fold (95% CI: 1.21, 6.22) greater odds of prediabetes, respectively.Conclusions: Elevated plasma Aβ40 and Aβ42 levels were associated with increased risk of prediabetes in human subjects, which may be through impairing insulin sensitivity in hepatocytes and myotubes and insulin secretion in pancreatic β-cells.